Estimating the labour market impacts of transport projects in Finland - Riukula Krista; Väänänen Touko (The Research Institute of the Finnish Economy (ETLA), 2024)
Effects on labour market outcomes are often referred to when discussing the wider economic benefits of transport projects. However, research on the topic in the Finnish context is scarce. Thus, proponents of transport projects may put exaggerated hopes on the labour market effects when arguing for the projects. This review aims to give researchers a good starting point for analyzing the labour market effects of transport projects in Finland. We review theoretical frameworks and recent empirical literature on the effects of transport projects and accessibility on the labour market. We discuss the available data sources in Finland and methodological considerations for analyzing causal effects. Furthermore, we explore the integration of labour market impacts into cost-benefit analyses considering, for example, the risk of double-counting benefits.
Keywords: R42; H43; J68; H54; 330; Transport project; Labour market; Wider economic impacts; Empirical research